Red blood cell alloimmunization and antigen matching in sickle cell disease – the African perspective - Natukunda, Bernard (ISBT Science Series, 2012)
In sickle cell disease (SCD), blood transfusion facilitates improved blood and tissue oxygenation, reduces the propensity to sickling by diluting host cells, and suppresses the production of red blood cells (RBCs) containing sickle haemoglobin (HbS). Delivery of RBC transfusions to patients with SCD varies by method (simple vs. exchange) and frequency (episodic vs. chronic). However, due to the genetic differences between blood donors and recipients, repeated transfusions increase the risk of developing alloantibodies to RBC antigens. The antigens most frequently involved belong to the Rh, Kell, Kidd, Duffy, Lewis, and MNS blood group systems. Consequences of RBC alloimmunization include delays and difficulties in obtaining compatible blood for future transfusions, the occurrence of delayed haemolytic transfusion reactions (DHTRs), the hyperhaemolysis syndrome and autoimmunization. In Europe and USA, RBC alloimmunization rates ranging from 18% to 76% have been reported in SCD while other multiply transfused (OMT) patients had alloimmunization rates of 5% to 20% indicating that SCD patients are at a higher risk of developing RBC alloantibodies. To prevent alloimmunization in SCD patients, the standard practice in Europe and USA is to determine their extended RBC phenotype (ABO, Rh, Kell, Kidd, Duffy, Lewis, MNS) before commencing transfusion therapy and perform antigen matching for C, E and K antigens for patients without prior alloantibody formation. However, in Africa, lower RBC alloimmunization prevalence rates of 6–10% have been reported in SCD patients and no differences were observed between SCD and OMT patients. This may be explained by the presumed high phenotypic compatibility between donors and SCD patients who were all Black Africans. Also, a low transfusion load (a median 3 U of blood were transfused) in SCD patients might have led to the poor response to alloantigenic challenge. Anti-K alloimmunization was notably rare among African SCD patients compared to anti-S. In many African countries, pretransfusion immunohaematologic testing includes neither the detection of RBC alloimmunization nor preventive antigen matching. Most transfusion laboratories are understaffed and underequipped; they perform ABO⁄D typing plus room temperature saline cross-matches and do not screen for RBC alloantibodies. Hence, immunized SCD patients are not diagnosed and do not have the opportunity of receiving antigen- negative blood. Furthermore, data on the occurrence of DHTRs are lacking. Introducing pre-transfusion RBC alloantibody screening in all African countries will significantly improve the transfusion management of SCD patients. A program of limited phenotype matching for C, E and S antigens is recommended to prevent additional alloantibody formation in immunized SCD patients in Africa.
Keywords: Africa; Alloimmunization; Antigen matching; Sickle cell disease